Case Study on CFD investigation of dense phase pneumatic conveying at a pipeline enlargement - Muhammad Rashdan, Mohammad Rohizat (2014)
Pneumatic conveying is being widely used by industry for their conveying system and the most critical problem that the system has is the corrosion of the pipeline. Some of the many engineers has develop a solution order to reduce the corrosion rate of the pipeline that is to increase the diameter of the pipe with objective to reduce the flow velocities as the flow velocities contribute the most in corroding the pipeline. By using Fluent 6.3.26 simulation program, ‘Eulerian’ Computational Fluid Dynamic (CFD) model, simulating the movement of the particles is possible and by varying the three different pipeline geometry; single bore, abrupt step, and gradual step, constructed using Gambit 2.4.6 from a pipe bore of 75-100 mm. The flow behaviour of plug of material passing through the pipeline is investigated. With 5x10-3 s time step, the solid volume fractions is recorded at 0.01 s of flow time at the point of enlargement and visualised throughout the pipe. Supported by 5 m/s air flow, the plug movement is illustrated showing that there is a potential of stagnant zone formation with the abrupt step enlargement geometry, and on the other hand, the gradual step shows a smooth dispersed particle flow without any potential of stagnant zone formation.